Research and Opportunities in Supply Chain Modeling: A Review - Chandrakumar M. Badole; Dr. Rakesh Jain; Dr. A.P.S. Rathore; Dr. Bimal Nepal (International Journal of Supply Chain Management, 2012)
Supply chain management (SCM) has a long history of incorporating elements of engineering, technology, and management. Extensive research is ongoing in all aspects of SCM. An important research objective is the development and verification of mathematical models. Case studies are used to test the validity of new models. During the past decade, SCM literature has greatly expanded. Considering this vast array of literature, a comprehensive review is appropriate. This paper presents an in-depth review of supply chain (SC) modeling literature. The approach will help researchers, academicians and practitioners alike to take a closer look at the growth, development and applicability of issues related to SC modeling. From the wide selection of 690 papers published in the various aspects of SC modeling during the past decade, 282 papers were selected for this review. Lastly, ten key areas have been identified for future research. KEY WORDS: Literature Review, Supply Chain Modeling, Review Framework, Future Research